Effect of Clitoria ternatea on Androgen Receptor: Molecular Docking Study - Kurniawati, Erna Yovi; Muhlida, Vinilia Ihramatul (Infomasi dan Promosi Kesehatan, 2025)
Introduction: Polycystic Ovary Syndrome (PCOS) is a complex hormonal disorder that affects many women worldwide, characterized in part by elevated androgen levels that can lead to various health complications. Traditional medicinal plants, such as Clitoria ternatea, have been explored as potential therapeutic agents for managing PCOS. Methods: This study employed an in silico approach to evaluate the interaction between active compounds in Clitoria ternatea and the androgen receptor. Molecular docking, molecular dynamics simulations, and binding affinity analyses were conducted to assess the potential of these compounds in modulating androgen receptor activity Results: The computational analysis revealed that several active compounds in Clitoria ternatea exhibited favorable binding interactions with the androgen receptor, indicating a potential to modulate its activity. These compounds demonstrated stable interactions and promising binding energies in the molecular simulations. Conclusion These findings suggest that Clitoria ternatea may play a role in managing PCOS through modulation of androgen receptor activity. However, further in vitro and in vivo studies are required to validate these computational results and explore their therapeutic potential in clinical settings.